Toxicarioside A inhibits SGC-7901 proliferation, migration and invasion via NF-κB/bFGF signaling - Guo, Jun-Li (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate the inhibitory role of toxicarioside A on the gastric cancer cell line human gastric cancer cell line (SGC-7901) and determine the underlying molecular mechanism. METHODS: After SGC-7901 cells were treated with toxicarioside A at various concentrations (0.5, 1.5, 4.5, 9.0 μg/mL) for 24 h or 48 h, cell viability was determined by 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide assay, and the motility and invasion of tumor cells were assessed by the Transwell chamber assay. Immunofluorescence staining, reverse transcription polymerase chain reaction and Western blotting were performed to detect the expression of basic fibroblast growth factor (bFGF) and fibroblast growth factor receptor-1 (FGFR1), and nuclear factor-kappa B (NF-κB) activation was examined by electrophoretic mobility shift assay. RESULTS: The results showed that toxicarioside A was capable of reducing cell viability, inhibiting cell growth, and suppressing cell migration and invasion activities in a time- and dose-dependent manner in SGC-7901 cells. Further analysis revealed that not only the expression of bFGF and its high-affinity receptor FGFR1 but also the NF-κB-DNA binding activity were effectively blocked by toxicarioside A in a dose-dependent manner compared with the control group (P < 0.05 or P < 0.01). Interestingly, application of the NF-κB specific inhibitor, pyrrolidinedithiocarbamate (PDTC), to SGC-7901 cells significantly potentized the toxicarioside A-induced down-regulation of bFGF compared with the control group (P < 0.05). CONCLUSION: These findings suggest that toxicarioside A has an anti-gastric cancer activity and this effect may be achieved partly through down-regulation of NF-κB and bFGF/FGFR1 signaling.